Learning Strategies at MI Muhammadiyah 5 Palirangan During Covid-19 Pandemic - Lina Rohmatun Nisa; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
The purpose of this scientific work is to describe the strategies applied at the MI Muhammadiyah 05 Palirangan school in learning during the covid'19 pandemic. This scientific work reviews various aspects, including: school history, learning strategies, descriptions of educational progress, and school education problems in the face of the covid'19 pandemic. The technique of collecting data in this study was through interviews with teachers of MI Muahmmadiyah 05 Palirangan, observation, and documentation. Based on the results of research at MI Muhammadiyah 05 Palirangan only apply some time in online or online teaching and learning activities, after that the teaching and learning process is carried out as usual, namely face to face. The impact that emerged due to the COVID-19 pandemic on education made the system and curriculum change. The curriculum is more shortened while not burdening students. The positive side of online or online learning includes: the value of technology is needed so that teachers must be good at developing learning through technology and collaboration between teachers and students' guardians.